Argon matrix Raman spectroscopic and aggregation model density function theoretical study of methyl isothiocyanate. (15th May 2019) - Liu, Maozhu; Zhao, Yanying; Wu, Fengqi; Wang, Huigang; Zheng, Xuming
Abstract: The Raman spectra for methyl isothiocyanate (MTC) isolated in an argon matrix at different annealing temperatures and MTC in carbon tetrachloride at different concentrations were collected separately. Concentration‐dependent properties were characterized, and no noncoincidence effect (NCE) was observed. Argon matrix isolated Raman spectra shows that, the SCNC stretching at 6K presents as one distinct peak, it separates into two peaks at 25–35 K and merges as one peak again above 40 K, whereas its frequency shifted to a lower wavenumber. Concentration‐dependent experiments showed the peak frequency of SCNC stretching shifted to a higher wavenumber when the concentrations decreased. Aggregated dimer structures were proposed to explain the MTC SCNC and CS vibrational concentration effects with no NCE phenomenon. Density functional theories were performed to calculate the monomer and dimer of MTC; the dimer structure can explain the experimental data well. The strong antiparallel head‐to‐tail vibrational coupling of the SCNC oscillators in neighbouring molecules accounts for the frequency shifts of the SCNC stretching. Abstract : Increasing the temperature makes the Argon‐isolated monomer collide into dimers; accordingly, the spectrum changes from a monomer pattern to a dimer, that is, νSCNC redshifts, which is in accordance with the situation of MTC concentration enhancement in solution.